2022
DOI: 10.3390/jcm11206016
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis in Systemic Lupus Erythematosus: From 2022 International GISEA/OEG Symposium

Abstract: Musculoskeletal involvement is one of the most common manifestations of systemic lupus erythematosus (SLE), with a negative impact on both quality of life and overall prognosis. SLE arthritis can be classified into three different subtypes, with different prevalence and characteristic biomarkers and MRI findings. Identifying the pathogenetic mechanisms underlying musculoskeletal manifestations’ development is crucial to develop therapeutic strategies to suppress synovial inflammation, prevent erosions and defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…It is projected that TB screening and treatment will save 66 million lives between 2000 and 2020. The most recent national TB patient cost survey found that more than one in two TB-affected households have costs that exceed 20% of their family income [ 73 ]. The global target of eliminating catastrophic expenditures associated with TB for patients or their households by 2020 was not achieved.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is projected that TB screening and treatment will save 66 million lives between 2000 and 2020. The most recent national TB patient cost survey found that more than one in two TB-affected households have costs that exceed 20% of their family income [ 73 ]. The global target of eliminating catastrophic expenditures associated with TB for patients or their households by 2020 was not achieved.…”
Section: Epidemiologymentioning
confidence: 99%
“…The global target of eliminating catastrophic expenditures associated with TB for patients or their households by 2020 was not achieved. By 2022, it will be necessary to spend US$ 13 billion per year on TB prevention, diagnosis, treatment, and care in order to fulfill the global objective set at the UN high-level meeting on TB in 2018 [ 73 ]. Ninety-eight percent of tuberculosis (TB) cases that are recorded take place in low- and middle-income countries (LMICs), where financing is much less than what is required.…”
Section: Epidemiologymentioning
confidence: 99%
“…In OS ADs, the immune response is directed toward single-organ antigens. The most common OS AD is autoimmune thyroid disease (AITD) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLE can cause significant disability, multiplying the morbidity and mortality risks of patients [ 5 , 6 , 7 ], with the juvenile-onset form being associated with even greater mortality risk compared to the adult form [ 8 ]. Common clinical manifestations involve fever, joint pain and arthritis, oral ulcerations, alopecia, malar rash, photosensitivity, and Raynaud’s phenomenon [ 9 , 10 , 11 , 12 , 13 ]. Organ-system involvement in SLE can include the musculoskeletal system and the skin, the kidneys, lungs, heart, and many more [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%